Experiments in rheoplasis during sediment intrusion - Flint, A.; van de Poll, H.W.; Patel, I.M. (Atlantic Geology, 1983)
Injection of semi-fluid silt/water suspensions Into semi-fluid sand/cement slurries resulted In the formation of a variety of structures at the Interface between the two materials. These structures resemble flute, load, groove and rldga-caats and form as a result of flow-moulding ('rheoplasis')• These experimental results complement earlier work' on certain natural occurrences of these structures and substantiate the hypothesis that they form as a result of post-deposltlonal sediment movement and not through primary sedimentary processes.